2018
DOI: 10.1158/1078-0432.ccr-17-1444
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Directed against Cadherin RGD Exhibit Therapeutic Activity against Melanoma and Colorectal Cancer Metastasis

Abstract: New targets are required for the control of advanced metastatic disease. We investigated the use of cadherin RGD motifs, which activate the α2β1integrin pathway, as targets for the development of therapeutic monoclonal antibodies (mAb). Cadherin 17 (CDH17) fragments and peptides were prepared and used for immunization and antibody development. Antibodies were tested for inhibition of β1 integrin and cell adhesion, proliferation, and invasion assays using cell lines from different cancer types (colorectal, panc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…integrin activation to different extents in all tested cancer cell lines (colorectal, breast and [99]. The only exception is the CDH16 RGD sequence, which did not induce any integrin activation.…”
Section: Effect Of Flanking Sequences In Rgd Binding: Differences Betmentioning
confidence: 88%
See 2 more Smart Citations
“…integrin activation to different extents in all tested cancer cell lines (colorectal, breast and [99]. The only exception is the CDH16 RGD sequence, which did not induce any integrin activation.…”
Section: Effect Of Flanking Sequences In Rgd Binding: Differences Betmentioning
confidence: 88%
“…A simultaneous increased expression of CDH17 and the α2 integrin subunit, but an unchanged level of expression of the β1 integrin subunit, was reported for metastatic colorectal cancer cells, suggesting that these two proteins need to be increased to promote metastasis [44]. Proteomic analysis of the CDH17 interactome showed that α2, β1, α6, β4 and αv were the most abundant integrin subunits in metastatic KM12SM colorectal cancer cells [45], although α1 and α3 were also detected by flow cytometry in KM12SM cells, but not α4 and α5 [99]. No role was observed for the α6β4 integrin or the α1, α3 or αv subunits in the prometastatic properties of CDH17 in colorectal cancer cells.…”
Section: Rgd Cadherin-α2β1 Integrin Interactions In Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, adhesion, proliferation, invasion, and metastasis of colon cancer on collagen type I and IV and cadherin 17 were promoted through FAK‐mediated extracellular signal‐regulated kinase (ERK) activation (see Supporting Information Tables S3 and S4). Thus, same as collagen type I, it seems that induction of HT29 CSLCs on keratin substrate is mediated by FAK–ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 93%
“…Treatment of colorectal cancer or melanoma cells with an antibody targeting the cadherin-17 RGD motif reduced their metastatic potential in vivo. [23] Inhibiting tumor-platelet crosstalk is a promising strategy to limit tumor progression and metastasis; RGD cadherins may be promising molecular targets.…”
Section: Discussionmentioning
confidence: 99%